Prevalence of Paternal Postpartum Depression in Anuradhapura District in Sri Lanka and Its Association With Maternal Postpartum Depression as a Risk Factor - Rukmali Siriwardhana; Madusha Somarathna; Maheshika Sooriyaarachchi; Sachini Subasinghe; Hasitha Sumanasekara; pyara Thalagala; Channaka Hapuarachchi; Jeewani Dinasena; Dhanushka Jeewantha Hewabostanthirige (Tehran University of Medical Sciences, 2022)
Objective: This study aimed to determine the prevalence of PPPD in Anuradhapura district, its association with maternal PPD, and relevant risk factors. Materials and methods: Cross sectional study was conducted among fathers in Anuradhapura district having infants 1-5 months by giving questionnaire specifically developed for the study with Edinburgh postnatal depression scale (EPDS) and self-constructed questions. Out of 6324 fathers, 435 fathers and their partners were randomly selected and proportionately allocated to 5 Medical Officer of Health (MOH) areas. R Program and SPSS have used for the data analysis. Results: Our results revealed that the PPPD prevalence is approximately 11% (95%CI: 8.08-14.67) based on cut off score of 7 points in the EPDS. PPPD was correlated with maternal PPD (OR 19.16, 95%CI 5.0473-85.1203), income decrement (OR 8.1571, 95%CI 2.4621-32.6289), increased time stayed at home in postpartum period (OR 3.7775, 95%CI 1.2365-13.8175).  But other parameters such as infant`s age, work time and number of children were not significantly influenced risk factors for PPPD. Conclusion: PPPD is prevalent in the Anuradhapura district and maternal postpartum depression has positively influenced. But currently, screening programmes for PPPD is lacking in Sri Lanka. Thus, these deficiencies urgently need to be addressed and should provide information and instructions to fathers regarding this new transition. However, these results need replication in more expanded case control study. Since the prevailing covid-19 pandemic at the time of data collection may have impacted the mental health of the fathers specially in countries like Sri Lanka, where mental health support is limited.